Annual World Bank Conference on Development Economics, 1995 edited by Michael Bruno and Boris Pleskovic.. - Bruno, Michael.; Pleskovic, Boris. (World Bank, 1996)
"The Annual World Bank Conference on Development Economics provides a forum for debate and the exchange of ideas and information between World Bank staff and development researchers and practitioners from around the world. The 1995 conference addresses four themes: (1) where we stand on inequality, poverty, and growth; (2) demographic change and development; (3) aid and development; and (4) fiscal decentralization."